2022
DOI: 10.3847/2041-8213/ac86d2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetar Engines in Fast Blue Optical Transients and Their Connections with SLSNe, SNe Ic-BL, and lGRBs

Abstract: We fit the multiband lightcurves of 40 fast blue optical transients (FBOTs) with the magnetar engine model. The mass of the FBOT ejecta, the initial spin period, and the polar magnetic field of the FBOT magnetars are respectively constrained to M ej … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 87 publications
0
30
0
Order By: Relevance
“…While these objects, primarily found in quiescent or poststarburst galaxies (Arcavi et al 2014;French et al 2020), constitute the most numerous and homogeneous class among TDEs, there exist a number of other transients that have been proposed to be due to tidal disruptions. These include objects found through their X-ray emission (Saxton et al 2020); objects found in active galactic nuclei (AGNs; explicitly excluded by the criteria of van Velzen et al 2020), such as PS16dtm (Blanchard et al 2017); objects found in luminous infrared galaxies often suffering considerable extinction (Tadhunter et al 2017;Mattila et al 2018); unique objects such as the superluminous ASASSN-15lh (Leloudas et al 2016), some of which are often debated to be of supernova or AGN origin (see Zabludoff et al 2021); or fast blue optical transients (FBOTs), such as AT 2018cow, whose nature is also debated (e.g., Kuin et al 2019;Perley et al 2019;Kremer et al 2021;Liu et al 2022;Metzger 2022).…”
Section: Introductionmentioning
confidence: 99%
“…While these objects, primarily found in quiescent or poststarburst galaxies (Arcavi et al 2014;French et al 2020), constitute the most numerous and homogeneous class among TDEs, there exist a number of other transients that have been proposed to be due to tidal disruptions. These include objects found through their X-ray emission (Saxton et al 2020); objects found in active galactic nuclei (AGNs; explicitly excluded by the criteria of van Velzen et al 2020), such as PS16dtm (Blanchard et al 2017); objects found in luminous infrared galaxies often suffering considerable extinction (Tadhunter et al 2017;Mattila et al 2018); unique objects such as the superluminous ASASSN-15lh (Leloudas et al 2016), some of which are often debated to be of supernova or AGN origin (see Zabludoff et al 2021); or fast blue optical transients (FBOTs), such as AT 2018cow, whose nature is also debated (e.g., Kuin et al 2019;Perley et al 2019;Kremer et al 2021;Liu et al 2022;Metzger 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the majority of TDEs are found by wide-field optical surveys and a distinct class of objects has been discovered where the optical/UV emission is dominated by a thermal component with black-body temperatures 2 − 4 × 10 4 K (van Velzen et al 2020). While these objects, primarily found in quiescent or post-starburst galaxies (Arcavi et al 2014;Kuin et al 2019;Kremer et al 2021;Metzger 2022;Liu et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 2018;Kuin et al 2019;Perley et al 2019;Metzger 2022), while the second category regards FBOTs as arising from the core collapse of massive stars. To power the rapid evolution, the collapsar models require ★ E-mail: n.sun@sheffield.ac.uk some special energy input by, e.g., magnetar (Prentice et al 2018;Fang et al 2019;Liu et al 2022), jets (Gottlieb, Tchekhovskoy, & Margutti 2022;Soker 2022), or the strong interaction between ejecta and circumstellar material (CSM; Fox & Smith 2019;Leung et al 2020;Xiang et al 2021). Many observational studies (Ho et al 2021;Xiang et al 2021) reveal the similarities in the light curves and spectra between FBOTs and the Type Ibn SNe (i.e.…”
Section: Introductionmentioning
confidence: 99%